The Values of Islamic Education Embodied in the Aceh Language Poetry Rateb Meutuwah - Rini Werdiningsih; Bertaria Sohnata Hutauruk; Martius Martius; Baktiar Nasution; Masrizal Mukhtar (Tafkir: Interdisciplinary Journal of Islamic Education, 2022)
Poetry is one of the media that can provide education to listeners and those who watch it if the poetry is also in visual form. However, there are also poems that are mere entertainment without educational value, especially in Islamic education. Therefore, it is necessary to study the value of education in a poem that the author takes as a sample poem in Acehnese entitled Rateb Meutuah. This study used a qualitative descriptive research method, collecting data using the document review method and the data content analysis method. The results of the research prove that the Aceh language poem Rateb Meutuwah sung by Joel Pasee is very closely related to the content of Islamic educational values, such as the value of humility (tawadhu'), the value of patience, the value the obligation to educate children, the value of advocating the five daily prayers, the value of devotion to both parents, the value of respect and devotion to teachers, and the value of advocating for children with good prayers. Thus the Aceh language poem Rateb Meutuwah is full of Islamic educational values, so it is highly recommended to always listen to or show it to children so that the contained educational values ​​can be instilled in a child.